Kajian Analisis Deskriptif Prinsip Spiritualitas Zakharia Sebagai Upaya Pembaharuan Formasi Rohani Kristen Masa Kini - Made Nopen Supriadi; Daniel Sarwono; Estherlina Maria Ayawaila (Sekolah Tinggi Teologi Arastamar Bengkulu, 2021)
This paper is a phenomenological descriptive analysis of the living conditions of Christians today. The author found several problems in the life of Christian spirituality today, namely: the failure of Christians to reflect on their spirituality by their religious positions, the emergence of an apathetic attitude to show a good spiritual life due to an experience of failure, a lack of practical implementation of the values ​​of spirituality that are understood, the life of spirituality. without obedience and the presence of a center of non-biblical spirituality in the Christian life. The writer observes this problem as a problem in building the spiritual formation of Christianity today. This problem the writer observed was also experienced by Zacharias, but the Bible provides the fact that Zacharias was able to overcome these problems. Thus this paper refers to the principle of Zacharias spirituality in answering this problem. Hopefully this article adds insight and provides answers to the lives of Christians today.